2018
DOI: 10.18632/oncotarget.24736
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-based signatures in cerebrospinal fluid as potential diagnostic tools for early stage Parkinson’s disease

Abstract: Parkinson’s Disease is the second most common neurodegenerative disorder, affecting 1–2% of the elderly population. Its diagnosis is still based on the identification of motor symptoms when a considerable number of dopaminergic neurons are already lost. The development of translatable biomarkers for accurate diagnosis at the earliest stages of PD is of extreme interest. Several microRNAs have been associated with PD pathophysiology. Consequently, microRNAs are emerging as potential biomarkers, especially due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 60 publications
5
76
1
2
Order By: Relevance
“…Of the 8 miRNAs that were differentially expressed between iPD and controls, 4 (50%) have been previously identified as deregulated in PD. These were miR-7-5p, 71 miR-22-3p, [72][73][74] miR-124-3p, 75 and miR-433-3p. 76 Another interesting finding is that the miRNAs found deregulated in genetic versus iPD cases were very different.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 8 miRNAs that were differentially expressed between iPD and controls, 4 (50%) have been previously identified as deregulated in PD. These were miR-7-5p, 71 miR-22-3p, [72][73][74] miR-124-3p, 75 and miR-433-3p. 76 Another interesting finding is that the miRNAs found deregulated in genetic versus iPD cases were very different.…”
Section: Discussionmentioning
confidence: 99%
“…Shortcomings for biomarker research are the RNA input requirements for sequencing protocols as well as the still relatively high costs of NGS. Some studies demonstrate that downscaling is possible without losing sensitivity and specificity ( Burgos et al, 2013 , 2014 ; Rao et al, 2013 ; dos Santos et al, 2018 ). As NGS is still a relatively new technique and the solutions for small RNA sequencing are continuously improved, it is likely that this technique will be more widely available in the future.…”
Section: Sources Technical Considerations and Biomarker Potential Ofmentioning
confidence: 99%
“…Thereof, 6 miRNAs were further validated based on their involvement in related signaling pathways: miR-1, miR-19b-3p showed decreased expression in PD, while miR-153, miR-409-3p, miR-10a-5p, and let-7g-3p were found upregulated. A recent study reported that 5 miRNAs were able to differentiate between early stage PD and healthy controls: miR-151a-3p and let-7f-5p were up-regulated in PD CSF, whereas miR-27a-3p, miR-125a-5p, and miR-423-5p were significantly decreased ( dos Santos et al, 2018 ). The different studies performed with total CSF or CSF-exosomes show no overlapping results, even though the cohorts were of a comparable size.…”
Section: Circulating Mirnas As Biomarkers In Parkinson’s Diseasementioning
confidence: 99%
“…53 Another study demonstrated that miR-423-5p in cerebrospinal fluid can be selected as one of the members of Parkinson's biomarker panel. 54 In the current study, we truncated the 3ʹUTR of the GRIN1 gene, and initially confirmed the potential functional sequence of the 3ʹ regulatory region of the GRIN1 gene by means of the luciferase reporter assay. Although bioinformatics tools showed the presence of multiple miRNA binding sites in the +295 bp -+ 497 bp region, including miR-212-5p, miR-324-3p and miR-326, further overexpression experiments did not directly demonstrate the regulatory effect of these miRNAs on GRIN1 gene expression.…”
Section: Dovepressmentioning
confidence: 67%